(untitled) (Medico Legal Update, 2021)
Background: Several clinical trials on cancer showed a correlation between elevated levels of regulatory T cells with either poor prognosis or poor response to some therapies. Hence, in this study we tried to measure the regulatory T cells (CD4+CD245+) count and to evaluate the program death receptor 1(PD1) as a one of the main suppressive mechanisms that regulatory T cells use in CML patients with different molecular response to imatinib therapy. Method: Flow cytometry technique was used to analyze 30 sample of optimal molecular response of CML patients (BCR-ABL transcripts ? 0.1%) and 30 sample of failure molecular response patients (BCR-ABL transcripts >1%) with or without hematological failure, in order to assess the CD4+CD25+ T cells (Tregs) and PD1 expression on these cells. Thirty samples age and gender matched were used as healthy controls. Results: A high proportion of CD4+CD25+ T cells was found in failure groups compared to control and optimal groups(P= <0.001), while there was no significant difference between control and optimal groups with (P= 0.481). A cutoff value of CD4+CD25+ T cells at >33.7 % was highly significant with high sensitivity and specificity. This value can be used to determine the failure from the optimal CML responders. There was no noticeable differences (P= 0.125) in PD1+ expression among CD4+CD25+ T cells. Conclusion: A high percentage of Treg cells in the failure CML group might be an indication of immune escape of leukemic cells in those patients compared to the other investigated groups.